Digital Marketing In Public Institutions - Benamara, Ahmed; Mehjoubi, Med Lakhar; Fatiha ,Abid (جامعة الوادي University of Eloued, 2025)
Digital marketing is essential for public institutions to improve communication, engage citizens, deliver services efficiently, and reduce costs. Key strategies include using social media for real-time updates, optimizing websites and apps for better user experience, and running targeted email campaigns. Challenges such as resistance to technology, lack of infrastructure, and data security concerns can be addressed with training, modern infrastructure, and adherence to privacy regulations. By implementing these strategies, public institutions can effectively connect with citizens, enhance participation, and ensure secure, cost-effective service delivery
Digital Marketing in Public Institutions: A Comprehensive Approach to Digital Transformation and Citizen Engagement
Keywords: Digital Marketing; Public Institutions